Biological efficiency and evaluation of bioactive compounds of wild mexican strains of Hericium erinaceus - Páez-Olivan, Laura; Quiñones, Carmen; Naranjo, Néstor; Torres, René; Correa-Ramírez, Miguel; Herrera, Jaime (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The basidiomycete Hericium erinaceus is one of the most consumed edibles and medicinal mushrooms in the world and appreciated in traditional Chinese medicine. In Mexico it is known as lion’s mane. The biological efficiency of wild strains of H. erinaceus cultivated in different substrates in the Durango region, mainly agave bagasse, a waste from mezcal production, was evaluated. The CCH003 strain from Espinazo del diablo showed the highest biological efficiency of 42.33 % and a productivity rate of 0.47 %, with a total cultivation period of 90 days and three harvests. Regarding the evaluation of bioactive compounds, the same strain obtained significant differences compared to the others, it presented the highest values for all determinations; 60 ± 0.018 mg EAG.g ES-1 in phenolic content, 4.21 ± 0.013 mg EQ.g ES-1 for flavonoids, 71.16 ± 0.002 mg EAA.g ES-1 in CAT, 0.0012 ± 0.001 mg AA.g ES-1 for by ABTS and 121 ± 0.107 µg EAG.mL-1 by DPPH. The variability of the results in the tests carried out provides information on how the type of substrate, climatological and geographical conditions and stage of maturity influence the development of the fungus, including the production of secondary metabolites, even if it is the same species. It is expected that this information will be useful to promote the use of agave bagasse as a substrate in the cultivation of H. erinaceus and thereby diversify rural activities in the region, and in the future generate new studies on the effect of conditions on the production of bioactive compounds.